Pharmacist-led counseling on insulin pens: A pre-post study in Nguyen Tri Phuong Hospital - Tran, Truong Phu Khanh; Nguyen, Huynh Thao Vy; Nguyen, Duc Quynh Chau; Vo, Thi Ha (Tạp chí Y Dược Huế, 2025)
Background: Improper insulin pen use remains a significant barrier to optimal glycemic control, leading to treatment inefficacy and increased risk of complications. This study aimed to evaluate the impact of pharmacist-led counseling on outpatients’ knowledge, attitude, and practice (KAP) regarding insulin pen use at Nguyen Tri Phuong Hospital. Materials and methods: A pre-post intervention study was conducted with 127 post-intervention patients out of 219 pre-interventions in a month (10 - 11/2022). Results: 219 patients participated in the consultation, and 127 were research subjects. After the intervention, patients with good knowledge, positive attitude, and good practice increased significantly from 57.5% to 91.3%. (p<0.001), from 78.7% to 93.7% (p<0.001), and from 43.3% to 88.2% (p<0.001), respectively. Correct steps increased strongly were “perform a safety test or air shot” (from 18.9 - 24.4% to 69.3 - 76.4%), “keeping the injection button at the injection site for at least 5 seconds” (from 46.5% to 89.8%), and “remove and discard the needle” (from 17.3% to 67.7%). Conclusions: Pharmacist-led counseling significantly improved patients’ knowledge, attitude, and practice regarding insulin pen use.